Diseño del sistema de gestión para demostrar la carbono neutralidad del Centro de Acopio la Sylvia - Calderón-Vargas, Ericka Vanessa (Instituto Tecnológico de Costa Rica, 2016)
The climate change that the planet has suffered generates serious consequences for the environment, society and economy; that is why companies must control and reduce their emissions. As a contribution to the solution of this problem, the Sylvia Collection Center required to design a management system to demonstrate its Carbon Neutrality. It was used the methodology proposed in the national standard INTE - 12-01-06: 2011 which consists of determining the Carbon Footprint of the company, as well as; establishing reduction measures improve their environmental performance and to propose compensation options so that the company can be Carbon Neutral. It was determined that the Carbon Footprint for the base year was 1 365 ton CO2e where the solid wastes were the largest component with a 58.8% followed by the emissions from fossil fuels with a 38% and other sources with a 3.2%. To achieve a reduction of the solid waste, a change in the reception of materials is proposed by including a check list and to do a study of the waste composition that allows them indentify other valuable wastes. In the case of fossil fuels, it is necessary to establish a control and maintenance program of the vehicles; also, to do a study of movements and times that permits reorganization of the center and to change the vehicles in a long term. Furthermore, two alternatives are proposed to achieve the compensation components which are to acquire carbon credits by incorporating the terrain to the field payment program of the environmental services.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2016.
Keywords: Cambio climático; Huella de carbono; Centro de acopio; MINAE; INTECO